Fine-tuning inflammation-resolution programs: focus on atherosclerosis. Issue 2 (March 2017) - Fredman, Gabrielle; Sadhu, Sudeshna; Rymut, Nicholas
Abstract : Purpose of review: Nonresolving inflammation is now considered the underpinning of several prevalent human diseases, including atherosclerosis. The resolution of inflammation is a highly coordinated program to counterbalance proinflammatory signals for a swift return to tissue homeostasis. This process is controlled in part by endogenous specialized proresolving lipid mediators (SPMs). Emerging evidence has revealed that the balance of SPMs and proinflammatory mediators during acute inflammation regulates the duration of the inflammatory response and the timing of tissue resolution. Moreover, an imbalance between SPMs and proinflammatory mediators has been linked to several prevalent chronic inflammatory diseases in humans, including atherosclerosis. Recent findings: Lipid mediator imbalances have recently been linked to atherosclerotic plaque instability. Administration of key SPMs restored this imbalance and led to plaque stability. SPMs have also recently been shown to be protective in other cardiovascular disease models including myocardial infarction, stroke and neointimal hyperplasia. Summary: The current review highlights recent work that supports the concept of dysregulated inflammation-resolution in atherosclerosis with a particular focus on mechanisms and therapeutic opportunities associated with SPM receptors and lipid mediator imbalances. This article is based on experimental studies.